UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENINGGALAN SEJARAH MASA ISLAM DI INDONESIA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF (JIGSAW) BERBANTUAN MEDIA PUZZLE - Setyawaty, Putry Eka; Hanifah, Nurdinah; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
From the findings in the field, the results of learning IPS on the material of the historical heritage of Islam in Indonesia is still less than the maximum.As an effort to improve learning outcomes, a cooperative learning model (jigsaw) is supported by the puzzle media. Classroom Action Research Methods are performed with an implementation procedure that refers to the Kemmis Taggart spiral model. The instrument is a teacher performance observation sheet in planning and implementing learning, student activities, learning outcomes, and field notes. The results of action implementation, the percentage of teacher performance in planning cycle I 86%, cycle II and III reach the target that is 100%. Percentage of teacher performance in implementing cycle I 83%, cycle II 92,9%, and 100% cycle III. Percentage of student activity of cycle I 53%, cycle II 83%, and cycle III 90%. The percentage of learning result in preliminary data from 33 students only 9 people (27%) who complete the KKM is 70. A complete cycle of 18 students (60%), cycle II 26 people (86.7%), and cycle III 27 people (90%) exceeded the target of 82%. Thus, through the application of cooperative learning model (jigsaw) media-assisted puzzle student learning outcomes on the material of Islamic heritage in Indonesia can be increased.